Real-life impact of uncontrolled severe asthma on mortality and healthcare use in adolescents and adults: findings from the retrospective, observational RESONANCE study in France - Pascal Demoly; Nicolas Roche; Vincent Perez; Gilles Garcia; Alexandre de Larrard; Charlotte Cancalon; Stève Bénard; Aymeric Mahieu; Laurine Vieu (BMJ Open, 2022)
Objective To characterise uncontrolled severe asthma and compare the disease burden with the general and asthmatic populations.Design Retrospective observational study using a national sample of a French healthcare database (Echantillon Généraliste des Bénéficiaires (EGB)).Setting The EGB, an anonymised permanent sample of health insurance databases, representing 1/97th of the French population.Participants Patients (≥12 years) were selected in year 2014 and followed 2 years. A cohort of patients with uncontrolled severe asthma was defined using an algorithm based on peer-reviewed literature and Global Initiative for Asthma recommendations. Index date was the occurrence of the first marker of uncontrolled asthma. This cohort was matched with two control cohorts, general population and asthmatic controls, on baseline characteristics.Main outcomes measures Mortality, healthcare use and associated costs were studied in the 2 years of follow-up.Results Among 467 716 individuals in the EGB, 16 588 patients with asthma were identified, including 739 (4.5%) with uncontrolled severe disease. The survival probability at 2 years for patients with uncontrolled severe asthma (92.0%) was lower than in the general population cohort (96.6%; relative risk of death: 2.35; 95% CI: 1.70 to 3.29; p<0.0001) and tended to be lower than in the control asthmatic cohort (94.3%; p=0.07). Emergency department visits and hospitalisations were higher in patients with uncontrolled severe asthma than in the general population (64.7% vs 34.9%; p<0.0001) and asthmatic controls (64.7% vs 55.2%; p=0.0002). Other components of healthcare use (medical and paramedical visits, medications) were increased in patients with uncontrolled severe asthma compared with control populations. These increases translated into higher costs (p<0.0001 for both comparisons).Conclusions This study demonstrates the huge burden of uncontrolled severe asthma in terms of mortality, morbidity and healthcare resource consumption compared with other patients with asthma and with the general population and emphasises the importance of appropriate management in this high-risk population.